2002
DOI: 10.1159/000063180
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Resection of a Fetal Pericardial Teratoma

Abstract: Objective: Pericardial teratomas are rare congenital tumors which invade the developing mediastinum, compressing the venous return to the heart, leading to hydrops. Tumors, with large cystic components, have been treated previously with in utero pericardiocentesis with some success. We present the first reported case of in utero open resection of a fetal pericardial teratoma. Methods: A 31-year-old G1P0 woman was found to have a fetus with a pericardial teratoma. Hydrops developed at 24 weeks’ gestation. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
0
37
1
3
Order By: Relevance
“…In comparison to others, teratoma occurs not in the heart, but with close contact with aorta or pulmonary artery 11,12 . Fetuses with teratoma are presenting various clinical symptoms, from asymptomatic, to mild pericadial effusion up to hydrops fetalis.…”
Section: Hydrops Testiscontrasting
confidence: 68%
See 1 more Smart Citation
“…In comparison to others, teratoma occurs not in the heart, but with close contact with aorta or pulmonary artery 11,12 . Fetuses with teratoma are presenting various clinical symptoms, from asymptomatic, to mild pericadial effusion up to hydrops fetalis.…”
Section: Hydrops Testiscontrasting
confidence: 68%
“…Yinon et al reported about 40 cases of fetuses with teratoma and none of them survived 13 . Sydorak et al described 31 year old patient, at 24 weeks of pregnancy with teratoma and in this case hydrops fetalis occured 11 .…”
Section: Hydrops Testismentioning
confidence: 70%
“…531,532 Open fetal surgery for extracardiac conditions affecting the heart such as resection of pericardial teratoma is possible. 533,534 Innovative open fetal surgical procedures that may be lifesaving to the fetus or may improve postnatal outcomes may be pursued on an investigational basis, but only once the benefits are carefully weighed against the risks to both fetus and mother.…”
mentioning
confidence: 99%
“…Van Selm et al [20] reported one eclamptic seizure and three cases of fetal demise despite intrauterine transfusions for immune hydrops. In an additional case of fetal cardiac compromise with pericardial teratoma fetal hydrops persisted despite in utero resection [21] . Over the course of 3 weeks evolving mirror syndrome led to an emergency cesarean section.…”
Section: Discussionmentioning
confidence: 92%